Bacteroid Development in Legume Nodules: Evolution of Mutual Benefit or of Sacrificial Victims? - Attila Kereszt; Peter Mergaert; Eva Kondorosi (Molecular Plant-Microbe Interactions, 2011)
Symbiosomes are organelle-like structures in the cytoplasm of legume nodule cells which are composed of the special, nitrogen-fixing forms of rhizobia called bacteroids, the peribacteroid space and the enveloping peribacteroid membrane of plant origin. The formation of these symbiosomes requires a complex and coordinated interaction between the two partners during all stages of nodule development as any failure in the differentiation of either symbiotic partner, the bacterium or the plant cell prevents the subsequent transcriptional and developmental steps resulting in early senescence of the nodules. Certain legume hosts impose irreversible terminal differentiation onto bacteria. In the inverted repeat–lacking clade (IRLC) of legumes, host dominance is achieved by nodule-specific cysteine-rich peptides that resemble defensin-like antimicrobial peptides, the known effector molecules of animal and plant innate immunity. This article provides an overview on the bacteroid and symbiosome development including the terminal differentiation of bacteria in IRLC legumes as well as the bacterial and plant genes and proteins participating in these processes.